Financial Aspects of Supporting Ukrainian Refugees - Krystyna GOMÓŁKA; Piotr KASPRZAK (Communications of International Proceedings, 2023)
Background: Warfare in Ukraine meant that in 2022 many countries, including Poland and other European, focused mainly on helping refugees from Ukraine and humanitarian transports. The assistance took on various forms - from basic humanitarian support, through in-kind help, financial and military assistance. Poland launched its humanitarian aid in the first days of the conflict. The aid provided by each country varies. It should be noted, however, that in each case it is possible to quantify it economically, i.e. to determine its scope, role and importance, and above all, its economic (financial) dimension. Objective: The aim of this article is to present various forms of assistance from European countries, with particular emphasis on Poland. However the main point was to focus on the financial aid provided by particular countries.  Materials and methods: As part of the research, the latest available literature on the subject, industry reports and sometimes press articles were used. Results: The aid provided varies depending on the analysed country. The research results, however, show that the greatest assistance was provided by countries directly bordering Ukraine (or located relatively close to its borders) and rich countries. For instance, the Polish government provided extensive assistance to refugees from Ukraine. It should be noted that this assistance is both temporary and long-term. The largest financial resources have been spent on education – PLN 4 billion. Practical implications: The results of the study can be used for further research and analysis. It is particularly important to determine the long-term effects and consequences of providing financial assistance to refugees from Ukraine.
Keywords: Ukraine; refugees; financial support; support; Poland